Ocular Decompression Retinopathy after Cataract Surgery in HLA-B27 Associated Anterior Uveitis. (17th November 2022) - Marchese, Alessandro; Cavalleri, Michele; Bandello, Francesco; Modorati, Giulio; Miserocchi, Elisabetta
ABSTRACT: Purpose: To describe the development and management of ocular decompression retinopathy after cataract surgery in a patient with chronic severe HLA-B27 associated anterior uveitis. Methods: Case report. Results: A 45-year-old woman affected by ankylosing spondylitis and HLA-B27 associated anterior uveitis was referred for left eye pain and inflammation one week after phacoemulsification and intraocular lens implantation. She had a history of anterior uveitis complicated by iris bombé for posterior synechiae and cataract. Intraocular pressure (IOP) prior surgery was 14 mmHg. Clinical examination after cataract surgery showed intense inflammation in the anterior chamber and marked hypotony. Fundus examination revealed the presence of ocular decompression retinopathy. High-dose corticosteroids were supplemented to control the uveitis, with a progressive IOP increase and resolution of retinal hemorrhages over the following months. Conclusion: Ocular decompression retinopathy may present after cataract surgery in patients with complicated HLA-B27 associated anterior uveitis who develop severe post-surgical hypotony and inflammation. Close monitoring of IOP and intraocular inflammation are warranted to prevent severe complications after cataract surgery in these patients.